Plasma pro-inflammatory cytokines, IgM-uria and cardiovascular events in patients with chest pain: A comparative study. (17th November 2015) - Tofik, Rafid; Swärd, Per; Ekelund, Ulf; Struglics, André; Torffvit, Ole; Rippe, Bengt; Bakoush, Omran
Abstract : Background. Risk stratification of patients presenting with acute chest pain is crucial for immediate and long-term management. Traditional predictors are suboptimal; therefore inflammatory biomarkers are studied for clinical assessment of patients at risk. Recently, we reported the association of IgM-uria with worse cardiovascular outcome in patients with acute chest pain. In this study, in the same cohort of patients with chest pain, we compared the value of IgM-uria to pro-inflammatory cytokines in predicting the occurrence of subsequent cardiovascular events. Methods. A total of 178 consecutive patients presenting with acute chest pain to the emergency department at the University Hospital of Lund, were recruited. Twenty-seven of 57 patients with acute coronary syndrome (ACS), and 18 of 118 patients with non-specific chest pain at baseline developed a subsequent major cardiovascular event during the 18 months follow-up. Urinary proteins (IgM-uria and Microalbuminuria) and plasma inflammatory markers (IL-6, Il-8, IL-10, IFN-γ and TNF-α) were measured at time of admission. Results. Using the receiver operating characteristic curves, the area under the curve for predicting cardiovascular events was 0.71 (95%CI 0.61–0.81) for IgM-uria, 0.61 (95%CI 0.51–0.71) for IL-6, 0.63 (95%CI 0.53–0.72) for IL-8, 0.65 (95%CI 0.56–0.74) for IL-10, and 0.64 (95% CI 0.54–0.74) for TNF-α. In multivariate Cox-regression analysis adjusted for age, microalbuminuria, IgM-uria, IL-10, TNF-α, troponin T, hsCRP and ACS at baseline; IgM-uria was the only biomarker that remained an independent predictor of outcome (HR = 4.2, 95%CI 2.2–7.8, p < 0.001). Conclusion. In patients with chest pain with or without acute coronary syndrome, IgM-uria could better predict the occurrence of cardiovascular events than plasma pro-inflammatory cytokines.